Jiménez Guirao, Jordi (ed.) (2021). Tres mirades sobre Hegel - Clàudia Sánchez Vidal (Enrahonar: Quaderns de Filosofia, 2023)
Jiménez Guirao, Jordi (ed.) (2021) Tres mirades sobre Hegel Sabadell: Edicions Enoanda, 91 p. ISBN 978-84-123469-4-7